POTENSI PREBIOTIC DARI EKSTRAK JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) - Setyawan, Ryan Haryo; Saskiawan, Iwan; Widhyastuti, Nunuk; Kasirah, Kasirah; Mulyadi, Mulyadi (Berita Biologi, 2023)
Nowadays, people are more aware of a healthy lifestyle and demand more functional food products. It leads to the raising of prebiotics and their health benefit, such as maintaining digestive tract health, decreasing heart disease and obesity risk, and improving the immune system. Since people need to diversify healthy food product, the pursuit of novel prebiotic ingredient which is potentially incorporated into functional food product needs to be done. One substance that has potency is β-glucan from white oyster mushroom or Pleurotus ostreatus. Accordingly, the aim of this study is to observe the prebiotic potency of white oyster mushroom extract. The study started by extracting β-glucan from white oyster mushroom powder by hot water extraction and subsequently proceeded into alkaline extraction. After that, β-glucan content of extracts and residue were measured by Megazyme® β-glucan assay kit and supplemented in glucose-free growth media to see whether it can be utilized by probiotic Lactobacillus plantarum Dad-13 and pathogen Escherichia coli InaCC B-4. After prebiotic index, prebiotic activity score, pH, and titratable acidity of each extract were compared to FOS and inulin, it showed that β-glucan from water extract of P. ostreatus has the potency to become a novel prebiotic substance. It has 37.15+1.27 g/100g β-glucan content, 1.42+0.05 prebiotic index, and 0.91+0.01 prebiotic activity score. It could be utilized by probiotic to produce organic acid, such as lactic acid as well.